Employee motivation profile for job enrichment - Adrian Tobias Teuber (Journal of Applied Leadership and Management, 2019)
Research questions: The aim of this article is the prediction of the employee's willingness to take over enriched tasks. Which characteristics of intrinsic or achievement motivation lead to which willingness to take over new and additional tasks, and what kind of tasks? Methods: The dimensions of intrinsic motivation, achievement motivation and job enrichment, as well as the corresponding sub-dimensions were defined to measure the employee's current motivation profile and its level of demand for enriched tasks. The data were collected with an online survey within a German machinery company (N = 66). Afterwards, the sample and the questionnaire were verified and with the collected data, correlation and linear regression analyses were performed. Results: The idea to derive the demand for job enrichment activities from the current intrinsic or achievement motivation profile was not fully supported. Whereas, additional analyses within the job enrichment dimension showed highly significant and positive correlations among all job enrichment sub-dimensions.
Keywords: 650